Social Behavior of the City Government and Citizens of the Metropolis during a Pandemic (for Example St Petersburg) - S. M. Eliseev; V. A. Glukhikh (Дискурс, 2021)
Introduction. The coronavirus has become a serious test for national and regional power and management systems. Many systems have demonstrated their effectiveness and flexibility, competence and coherence. But there were also cases when erroneous decisions were made at the regional and even national levels. The purpose of this article is to determine the main trends in changes in the social behavior of the city government and citizens of St Petersburg in the context of the coronavirus pandemic.Methodology and sources. The article is based on classical and modern theories of urban sociology, sociology of the formation and functioning of public spaces and public life in a modern city, data from urban statistics on COVID incidence and empirical observations.Results and discussion. From the very beginning, the city government of Saint Petersburg became the center of coordination and mobilization of all city resources to overcome the pandemic. However, it is not always possible to manage the available resources correctly and effectively. One of the reasons for the inefficient use of available resources was that the government did not define a strategy to combat the coronavirus pandemic from the very beginning. Decisions were made situationally, sometimes inconsistently. It is worth noting that, despite the restrictions imposed, the social behavior patterns of a significant part of citizens have not changed significantly, but have only been transformed into hybrid social practices.Conclusion. The study described the existing normative and hybrid models of social behavior of the government and citizens in the public space of the city in the context of the coronavirus pandemic, identified the most affected types of social relations (local-local) and local spaces (trade, entertainment, etc.) in which new social norms are most often violated.